ELLIPSIS IN ENGLISH AS FOUND IN SHERMAN ALEXEI’S NOVEL RESERVATION BLUES - Bonar Gurning; Darvin Sibarani (Muse: Jurnal of Art, 2023)
This research is about Ellipsis in English As Found in Sherman Alexei's Novel Reservation Blues.The objectives of the research are (1) To find out the types of ellipsis used in the sentences in Sherman Alexei's Novel Reservation Blues. (2) To find out the most dominant types of ellipsis used in the sentences in Sherman Alexei's Novel Reservation Blues. In analyzing the data, the researchers applied the theory of Halliday and Hasan (1976). The number of the data is 115 data. The result of the analysis shows that the ellipsis found in Sherman Alexei's Novel Reservation Blues is dominated by verbal ellipsis that is forty four utterances or 38.2 % then comes clausal ellipsis that is forty utterances or 35 %. The least is nominal ellipsis that is thirty one utterances or 27 %.